A CASE OF MASSIVE PERICARDIAL EFFUSION IN SUBCLINICAL HYPOTHYROIDISM - Devi, Sarojini; Chen, Yit Hern; Lee, Siow Ping (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Hypothyroidism is associated with multiorgan involvement and various complications. Pericardial effusion is a rare complication of hypothyroidism. However, if left untreated, it may progress to critical, life-threatening conditions such as cardiac tamponade and hemodynamic instability. Early identification of the diagnosis, with effective management of pericardial effusion in hypothyroidism, is essential. CASE A 67-year-old female with hypothyroidism since 2016 presented with worsening exertional dyspnoea, bilateral lower limb swelling, and fatigue. She had a background history of hypertension and bronchial asthma. She had elevated jugular venous pressure, but no muffled heart sounds. Her ECG showed small-voltage QRS complexes, and chest X-ray revealed cardiomegaly with pulmonary congestion. Her echocardiography showed a large pericardial effusion with a collapse of the right ventricle. An urgent pericardiocentesis was performed, and her symptoms improved after draining 500 cc of pericardial fluid. TFT showed elevated TSH (83.42 m IU/L) with normal free T4 (13.5 pmol/L). She had markedly elevated anti-thyroid peroxidase (>600 IU/mL) and anti-thyroglobulin (>4000 IU/mL). Her pericardial fluid investigations were unremarkable. The patient has been taking her levothyroxine inconsistently with her meals. Her levothyroxine dose was increased from 100 mcg to 150 mcg daily. She showed improvement by the third day of hospitalisation. She was discharged and advised to adhere to the levothyroxine. Her subsequent TFTs normalised with normal echocardiography during the follow-up visit. Hypothyroidism causes protein-rich pericardial effusion due to increased membrane permeability, increased albumin distribution volume, and diminished lymphatic drainage, which happens gradually over time. CONCLUSION Pericardial effusion in hypothyroidism is an infrequent entity. It is more frequent in long-standing clinical hypothyroidism than subclinical hypothyroidism. An early cardiac assessment, adequate thyroid replacement therapy, and medication adherence can help mitigate the risk of pericardial effusion or cardiac tamponade.